2016
DOI: 10.7717/peerj.1963
|View full text |Cite
|
Sign up to set email alerts
|

Shallow water heterobranch sea slugs (Gastropoda: Heterobranchia) from the Región de Atacama, northern Chile

Abstract: The coast of northern Chile has been sparsely studied in regards to its invertebrate fauna, with just a few works reviewing the distribution of local mollusks. This work presents a survey of the shallow water heterobranch sea slugs currently occurring around the port of Caldera (27 °S), in the Región de Atacama, northern Chile. Eight species of sea slugs were found in this study: Aplysiopsis cf. brattstroemi (Marcus, 1959), Baptodoris peruviana (d’Orbigny, 1837), Diaulula variolata (d’Orbigny, 1837), Doris fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Considering the present record-and further unpublished records of Ischnochiton pusio (Sowerby I, 1832) and Tonicia swainsoni (Sowerby in Broderip and Sowerby, 1832) from the same areas-the polyplacophoran diversity of northern and southern Chile may be similarly rich in species, even when considering the vast differences in the geographic and oceanographic conditions along the long Chilean coast (Osorio and Reid, 2004;Aldea and Valdovinos, 2005;Schwabe et al, 2006). Further field studies such as those by Reiswig and Araya (2014), Sirenko (2014Sirenko ( , 2015, Araya and Aliaga (2015), Araya et al (2016), Araya (2016), and Araya and Valdés (2016), which have revealed several new records or even new species in northern Chile, are thus essential to document this fauna.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Considering the present record-and further unpublished records of Ischnochiton pusio (Sowerby I, 1832) and Tonicia swainsoni (Sowerby in Broderip and Sowerby, 1832) from the same areas-the polyplacophoran diversity of northern and southern Chile may be similarly rich in species, even when considering the vast differences in the geographic and oceanographic conditions along the long Chilean coast (Osorio and Reid, 2004;Aldea and Valdovinos, 2005;Schwabe et al, 2006). Further field studies such as those by Reiswig and Araya (2014), Sirenko (2014Sirenko ( , 2015, Araya and Aliaga (2015), Araya et al (2016), Araya (2016), and Araya and Valdés (2016), which have revealed several new records or even new species in northern Chile, are thus essential to document this fauna.…”
mentioning
confidence: 62%
“…Further field studies such as those by Reiswig and Araya (2014), Sirenko (2014Sirenko ( , 2015, Araya and Aliaga (2015), Araya et al (2016), Araya (2016), and Araya and Valdés (2016), which have revealed several new records or even new species in northern Chile, are thus essential to document this fauna.…”
mentioning
confidence: 99%
“…Other reports (occurrences) for this species in the Peruvian coast are Playa Tartacay (El Paraíso, Huaura, Lima, 11°13'44.9"S) ( Zanabria 2020e ), Isla Chuncho (Pucusana, Lima, 12°28'S) ( Guzman 2018a ; Cuba 2019 ) and Puerto General San Martín (Paracas Bay, Pisco, Ica, 13°48'37.3"S) ( Zanabria 2020d ). In Chile, it was reported in Playa Brava (Caldera, Atacama, 27°03'S), Calderilla (Atacama, 27°05'S) ( Araya and Valdés 2016 ), Punta Blanca (Arica, 18°29'S), Comau Fjord (42°15'S), and Melinka (Guaitecas islands, Chilean fjord region, 43°52'S) ( Schrödl 2003 ). Other reports (occurrences) for this species in the Chilean coast include Chascos Bay (Copiapó, Atacama, 27°40'S), Reserva Nacional Pingüino de Humboldt (Huasco, Atacama, 29°01'S), Coquimbo (29°58'S), Valparaíso (33°21'S), Concepción (36°45'S), Valdivia (39°57'S), and Chiloé (41°53'S) ( iNaturalist 2023a ).…”
Section: Resultsmentioning
confidence: 99%
“…comm.) to Strait of Magellan (Chile, 53°S) and Peninsula Valdés (Argentina, 42°S) ( Schrödl and Millen 2001 ; Uribe et al 2013 ; Araya and Valdés 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation